2022
DOI: 10.1159/000521861
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hypertension among Patients on Peritoneal Dialysis Using Standardized Office and Ambulatory Blood Pressure Recordings

Abstract: <b><i>Introduction:</i></b> Prior studies conducted in peritoneal dialysis (PD) patients in the late 1990s provided considerably variable estimates of the prevalence and control of hypertension. The present study aimed to investigate the current state of hypertension management in this high-risk population. <b><i>Methods:</i></b> In 140 stable PD patients, we performed standardized automated office blood pressure (BP) measurements and 24-h ambulatory BP monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…‘Traditional’ CVD risk factors, including hypertension, dyslipidaemia and diabetes mellitus, are frequently present in patients with kidney disease. For example, in a cross-sectional study involving four PD centres in Greece, 95% of patients receiving PD had ambulatory hypertension and adequate blood pressure control was only achieved in 38.3% of patients 51 . Second, kidney dysfunction itself is a risk factor for CVD, which is evident even among patients with mild kidney dysfunction 52 , and has been attributed to ‘non-traditional’ CVD risk factors, such as inflammation, endothelial dysfunction and calcification 53 .…”
Section: Clinical Pd Outcomes Across the Globementioning
confidence: 99%
“…‘Traditional’ CVD risk factors, including hypertension, dyslipidaemia and diabetes mellitus, are frequently present in patients with kidney disease. For example, in a cross-sectional study involving four PD centres in Greece, 95% of patients receiving PD had ambulatory hypertension and adequate blood pressure control was only achieved in 38.3% of patients 51 . Second, kidney dysfunction itself is a risk factor for CVD, which is evident even among patients with mild kidney dysfunction 52 , and has been attributed to ‘non-traditional’ CVD risk factors, such as inflammation, endothelial dysfunction and calcification 53 .…”
Section: Clinical Pd Outcomes Across the Globementioning
confidence: 99%
“…For example, among 1202 patients enrolled in the 1995 Peritoneal Dialysis Core Indicators Study, only 29% had an office systolic BP > 150 mmHg and 18% had a diastolic BP > 90 mmHg [44]. However, these earlier estimates are not accordant with the results of a recent analysis of 140 stable ESKD patients from four PD centers in Northern Greece showing a high burden of hypertension in the PD population as well [45]. In this study, the prevalence of hypertension was 92.9% using a diagnostic threshold of 140/90 mmHg for standardized office BP recordings, whereas the prevalence rate of hypertension was 95% when a threshold of 130/80 mmHg for 24-hour ambulatory BP was applied.…”
Section: Prevalence Treatment and Control Of Hypertensionmentioning
confidence: 87%
“…The vast majority of patients (92.1%) were taking antihypertensive medications. However, only 52.3% and 38.3% of hypertensives were adequately controlled using office BP measurements and ABPM, respectively [ 45 ]. Studies using a case–control design also showed that the mean levels and trajectories of ambulatory BP did not significantly differ when patients on PD were compared with age-, sex- and dialysis-vintage-matched controls on thrice-weekly hemodialysis [ 46 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Hypertension is the leading cause of worldwide mortality, responsible for over 40% of deaths from cardiovascular disease, type 2 diabetes, and chronic kidney disease, per the World Health Organization 1–5 . Over 50% of the complications of hypertension may be prevented through diet modifications 6–9 . Guidelines for treatment and control of hypertension by the American Heart Association have increasingly leveraged lifestyle recommendations in addition to pharmaceutical‐based therapy 1,3,10,11 .…”
Section: Introductionmentioning
confidence: 99%